KARAKTERISTIK SOSIS RASA AYAM DARI SURIMI IKAN LELE DUMBO (Clarias gariepinus) DENGAN PENAMBAHAN 106 ISOLAT PROTEIN KEDELAI - Djoko Poernomo; Pipih Suptijah; Nisa Nantami (Jurnal Pengolahan Hasil Perikanan Indonesia, 2011)
African catfish has potential to be processed become sausage because it contained highly protein. Soy protein isolate was use as binder. This research aims was to determined SPI concentration to produce high quality of fish sausage, analyzed the physical characteristics and nutritional value contained in fish sausage, and comparing with commercial sausage. The meat  was washed twice and obtained the yield 18,72%. SPI 13% was selected and gave better result on sausage production. The results of proximate analysis for the ash content of 1,60%, protein of 15,97%, fat of 0,61%, carbohydrate 2,22%, moisture content of 79,6% and the TPC 0.5x101 colony/g. Value of the comparison test objectively for gel strength, water holding capacity and emulsion stability were lower than commercial sausage. Catfish sausage was more preferred the commercial sausage on the parameters folding test, teeth cutting test, smell and taste. Protein and carbohydrate nutrient content of fish sausage African catfish superior to commercial sausage.Key words: frequency of washing, fish sausage, soy protein isolate